Pengaruh Praktik Sholat Khusyuk Dalam Kegiatan Pembinaan Psikospiritual Terhadap Konsentrasi Belajar Mahasiwa - Izzah, Lailatul (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2024)
The purpose of this study is to determine how Ma'had students at UIN Suska Riau's learning concentration is affected by the practice of solemn prayer in their psychospiritual growth. This is because pupils frequently struggle to focus when studying, which has a negative impact on learning outcomes. UIN Suska Riau's 133 Ma'had students served as samples for this quantitative study. The sample of 18–21-year-old male and female students was split up into five coaching class groups. A Likert scale model or questionnaire is used to gather data. The 42-statement solemn prayer scale has a Cronbach's alpha rating of 0.945, indicating that the instrument is dependable and dependable. However, the concentration scale consists of 18 items, and the Cronbach alpha reliability test results reached 0.745. The results of the research show that solemn prayer in spiritual formation activities has a positive and significant relationship with study concentration. With a correlation coefficient of 0.487 and a significance of 0.000, it can be concluded that solemn prayer has a significant relationship with study concentration. This shows that the practice of solemn prayer in psychospiritual development activities influences study concentration by 23.7% so that there are 76.3% other factors, such as internal factors, namely physical and spiritual, which originate from the student's mental condition as well as external factors, namely the environment and learning conditions.